ANALISIS PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP PRICE TO BOOK VALUE PADA INDUSTRI BARANG KUNSUMSI DI BEJ - Muljono, Muljono; Prasetyo, Prasetyo (Universitas Muhammadiyah Magelang, 2005)
Price to book value repesent one of variable which can be used for the decision making of in doing an invesment. Price to book value used to identify an sahre price by comparing with its book value. This research aim to test to return the research conducted by A.Y.B Santosa (1997) and also give the empirical evidence for factors influencing price to book value. This research is used to know the influence of factors fundamental that is : Dividend Payout Ratio, Financial Laverage, Earning Growth Rate, and Return On Equity to Price to Book Value. This Research also aim to know he most dominant variable its link by price is to book value. Data used in this research is secondary data that is in the form of data of time series-ross section consisted of by 10 companies deputizing taht is peripatetic company at industrial sector cunsumer goods. Method of data collecting use the method of purposing sampling. While technical analyze in this research use the technique analyze the doubled linear regresi to know the independent variable influence to variable of dependennya and technique analyze the correlation coefficient of parsial used to know the modt dominant independent variable dependennya. To test the hypothesis use the test F, the test t, and test the determinant which is entire/all its processing is conducted by using SPSS version 10.0 windows. Result of data analysis with the technique analyze the multiple linear regression indicate that by simultan is price to book value influenced by its his independent variable that is: Dividend Payout Ratio, Financial Laverage, Earning Growth Rate, and Return On Equity. Assess the Adjusted R2 of equal to 0,242 showing change PBV influenced by together equal to 24,2% by variable DPR.